TIC´S y su aporte en el desempeño laboral de las secretarias de la Universidad Técnica de Babahoyo, período académico 2021 - Balcázar Fernández, Jorge Limber (2022)
This case study focuses on ICTs and their contribution to the work performance of the secretaries of the Technical University of Babahoyo, academic period 2022; these technological tools contribute satisfactorily to the daily work carried out by the executives of the administrative tasks of this institution. Of higher studies. In this investigation, inefficient communication and little teamwork that the secretaries have been developing were detected, as well as the improper use of ICTs in administrative activities, thus limiting proactive work. To counteract this problem, training is considered for the administrative body of secretaries of the Faculty of Social Legal Sciences and Education of the UTB, with topics such as: use of ICTs and human relations, with this contribution the quality of the service.